Strategies for Adopting Information and Communication Technology among Micro, Small and Medium Enterprises (MSMES). - Janaki, Dr.S. (International Journal of Advanced Science and Technology, 2020)
The main objective of this study is to evaluate the factors that encourage, as well as those that remain a constraint to adopt Information and Communication Technology (ICT) among Micro, Small and Medium Enterprises (MSMEs). Information and communication technology adoption analysis is the process from the organization attributes, resulting in an action plan for carrying out the adoption of information and communication technology that is rooted in an organizational context and addresses issues of concern to the intended user. Based on the nature of this study has been classified as a descriptive research design. The researcher adopted stratified random sampling which allows the researcher to classify with different sectors for Micro, Small and Medium Enterprises (MSMEs) to measure the level of adoption of Information and Communication Technology (ICT). The highest mean value has been observed from the enterprises who consider that financial support is the major challenge for adopting information and communication technology with a mean value of 4.18. It implies that 83.6% of the enterprises agreed that financial support is the major challenge for adopting technology and secured the first rank for the adoption of ICT among MSMEs. Practical implications This study has identified the factors influencing information and communication technology adoption and challenges for ICT adoption and its impact on business performance. This would help the organisation to formulate the feasible plan to implement the information and communication technology adoption in MSMEs. Original/value The review of the existing literature indicates that to no comprehensive and analytical study has been carried out on the adoption of ICT among MSMEs concerning factors which influence technology adoption. Hence, this importance has been reflected in this studys. Keyword:. Technology Adoption, Information Intensity, Perceived Relative Advantages, Micro, small & medium business